Traces across the body: influence of music-dance synchrony on the observation of dance - Woolhouse, Matthew Harold; Lai, Rosemary (Frontiers in Human Neuroscience, 2014)
In previous studies investigating entrainment and person perception, synchronized movements were found to enhance memory for incidental person attributes. Although this effect is robust, including in dance, the process by which it is actuated are less well understood. In this study, two hypotheses are investigated: that enhanced memory for person attributes is the result of (1) increased gaze time between in-tempo dancers, and/or (2) greater attentional focus between in-tempo dancers. To explore these possible mechanisms in the context of observing dance, an eye-tracking study was conducted in which subjects watched videos of pairs of laterally positioned dancers; only one of the dancers was synchronized with the music, the other being asynchronous. The results were consistent with the first hypothesis—music-dance synchrony gives rise to increased visual inspection times. In addition, there was a preference for upper-body fixations over lower-body fixations across both synchronous and asynchronous conditions. A subsequent, single-dancer eye-tracking study investigated fixations across different body regions, including head, torso, legs and feet. Significantly greater dwell times were recorded for head than torso and legs; feet attracted significantly less dwell time than any other body region. Lastly, the study sought to identify dance gestures responsible for torso- and head-directed fixations. Specifically we asked whether there are features in dance that are specially designed to direct an observer’s gaze towards the face—the main “communicative portal” with respect to the transmission of intent, affect and empathy.